Value Network as Part of New Trends in Communication - Soviar, Jakub; Vodak, Josef (Communications - Scientific Letters of the University of Zilina, 2012)
This paper deals with the topic of value network importance for the new trends in communication. It describes the main definition of distribution and place, and their relations with the value network. The value network is described as a network of all relevant factors impacting the product where the product is in the network's centre. The case of Apple iPod is provided as an example of the value network. E-commerce and digital distribution are also described in the paper as new communication trends. Discussion deals with main text results and authors' opinions.
Keywords: marketing; management; value network; distribution; communication; new trends; innovations; point of sales; digital distribution; e-commerce